2002
DOI: 10.1002/j.2050-0416.2002.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Vigour In Relation To Heat Sensitivity And Heat Resistance In Barley Evaluated By Multivariate Data Analysis

Abstract: The vigour loss model based on normal distribution after artificially ageing by heat treatment of barley seeds developed by Ellis and Roberts and further developed at Carlsberg by Aastrup et al. introducing vigour potential (VP), does not adequately describe seed vigour for all barley samples. In a preliminary investigation we have identified heat-resistant barley samples. In this investigation we found untreated barley samples from the field where heat treatment as high as 68C for 4 h at 12% water content onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Our material with naturally aged samples shows no correlation between VP and GI (r = -0.20). In an earlier experiment 15 we found that the heat-sensitive samples had slightly higher values of GI compared to heatresistant samples. The difference was significant.…”
Section: Wmrk +Ivqmrexmsr -Rhi\ Xs Hiwgvmfi Zmksyvmentioning
confidence: 67%
See 4 more Smart Citations
“…Our material with naturally aged samples shows no correlation between VP and GI (r = -0.20). In an earlier experiment 15 we found that the heat-sensitive samples had slightly higher values of GI compared to heatresistant samples. The difference was significant.…”
Section: Wmrk +Ivqmrexmsr -Rhi\ Xs Hiwgvmfi Zmksyvmentioning
confidence: 67%
“…The large difference between heat-resistant and heatsensitive barley observed in this study in the variety "Alexis" and in other varieties 14,15 is an interesting phenomenon as such and needs an explanation. If heat resistance could be controlled in cereal stocks, heat treatment, for example against fungi or insects, might be feasible as an alternative to chemicals.…”
Section: LI Geywiw Sj Liex Wirwmxmzmx] Erh Viwmwxergimentioning
confidence: 75%
See 3 more Smart Citations